1999
DOI: 10.3109/10623329909053412
|View full text |Cite
|
Sign up to set email alerts
|

The Putative Mechanistic Basis for the Modulatory Role of Endothelin-1 in the Altered Vascular Tone Induced byTrypanosoma cruzi

Abstract: Chagas' disease, caused by Trypanosoma cruzi, is an important cause of heart disease in Latin America. T. cruzi-induced microvascular compromise, in turn, is thought to play a major role in chagasic heart disease. Previous in vitro studies have implicated endothelin-1 (ET-1) as a potentially important vasomodulator present in increased levels in the supernatant of T. cruzi infected cultured human umbilical vein endothelial cells (HUVEC). Thus, the goal of the present investigation was to further evaluate the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 51 publications
2
25
0
Order By: Relevance
“…Beneficial effects of enzyme inhibition were evidenced by monitoring histopathology, echocardiography, and cardiac magnetic resonance imaging. Moreover, when isolated rat aortic rings were incubated with supernatants from T. cruzi-infected human umbilical vein endothelial cell cultures the recorded steady-state magnitude of the ring contractions was significantly greater than those produced by supernatants from uninfected control cells (Tanowitz et al 1999). All of these observations are consistent with a possible role for ET-1 in inducing vasoconstriction and having a possible modulatory role in the vascular alterations that occur in Chagas heart disease.…”
Section: Endothelin-1 (Et-1) and Vasculopathy In Murine Chagas Diseasesupporting
confidence: 74%
“…Beneficial effects of enzyme inhibition were evidenced by monitoring histopathology, echocardiography, and cardiac magnetic resonance imaging. Moreover, when isolated rat aortic rings were incubated with supernatants from T. cruzi-infected human umbilical vein endothelial cell cultures the recorded steady-state magnitude of the ring contractions was significantly greater than those produced by supernatants from uninfected control cells (Tanowitz et al 1999). All of these observations are consistent with a possible role for ET-1 in inducing vasoconstriction and having a possible modulatory role in the vascular alterations that occur in Chagas heart disease.…”
Section: Endothelin-1 (Et-1) and Vasculopathy In Murine Chagas Diseasesupporting
confidence: 74%
“…In addition, verapamil attenuates the endothelin-mediated vasoconstriction accompanying this infection. 19 We then evaluated another murine model of T. cruzi infection, the NOS2 Ϫ/Ϫ mouse. Holscher and others 20 demonstrated that NOS2 mice are rapidly killed by the highly virulent Tulahuen strain of T. cruzi.…”
Section: Discussionmentioning
confidence: 99%
“…All of these pathways are crucial in the development of cardiovascular dysfunction. Previous observations from our laboratory and others have implicated ET-1 in the vasculopathy associated with T. cruzi infection (2,31,32,52,57).…”
mentioning
confidence: 96%